A Study of Thermal Behaviour of HTS Devices at Alternating Current - Vadim Z. Manusov; Dmitrij Olegovich Krjukov (Institute of Advanced Engineering and Science, 2018)
The paper presents a study on thermal behavior of a coil made of a high-temperature supercon-ducting tape representing operation of a superconducting device (for example, a transformer). Based on the results of a physical experiment, a mathematical model of superconducting coil op-eration under short circuit conditions at the load side was developed. Regimes of overheating by variable short circuit currents were investigated. In this case, short circuit current amplitudes ex-ceeded a critical current of a superconductor, and coil parameters (e.g. an average nonlinearity parameter of a current-voltage characteristic, a superconductor length, and others) were varied. Permissible overheating for a coil with the possibility of its return into the superconducting state after emergency conditions in a dead-time period of automatic reclosing was considered. A crite-rion for return of a superconducting device into the superconducting state within a dead-time period of automatic reclosing has been obtained.